Reimagining Delilah's afterlives as femme fatale: the lost seduction - Blyth, Caroline (Library of Hebrew bible/Old Testament studies, 2020)
Chapter 1: The femme fatale: cultural icon -- Chapter 2: Mind the gap part 1: Delilah's interpretive afterlives -- Chapter 3: Mind the gap part 2: Delilah's cultural afterlives -- Chapter 4: Delilah redux.